The “Cow-mouth” Footwear from Coffin no. 7 in the Presbytery of the St Nicholas Church in Gniew (Poland) - Kozłowski, Tomasz; Nowosad, Wiesław; Nalaskowski, Filip; Grupa, Dawid; Grupa, Małgorzata (the Authors, 2023)
This article presents a comprehensive analysis of a pair of shoes excavated during archaeological research in the chancel of the St. Nicholas Church in Gniew, found on the feet of a man over 60. It is the first pair of Renaissance “cow-mouth” type shoes excavated from a grave. The results of the study of both archaeological material (footwear, velvet headgear covered with embroidery using threads in a metal braid) and iconography – portrait depictions, group scenes, and archival sources – confirmed the high social status of the deceased.
Keywords: Renaissance; footwear; markers; social differentiation; Gniew; Poland